ANN as a tool for medical prognosis - Abdul-Kareem, S.; Baba, S.; Zubairi, Y.Z.; Wahid, M.I.A. (2000)
The analysis of cancer survival is used to determine the efficiency of treatment programmes and protocols; it is also used to determine the type of treatment. At the individual level a prediction of cancer survival can help patients make informed decisions with regards to their quality of life and future finances. Currently available prediction methods apply to groups of people, and may not be adequate to predict treatment outcome for individual patients. This paper presents a conceptual model of a cancer knowledge base incorporating a computer-based predictor for survival. It proposes the use of an artificial neural network (ANN) as an alternative tool for investigating cancer survival. The focus of this research will be on nasopharyngeal carcinoma survival data collected in Malaysia.